Numerical Modeling and Experimental Investigation of the Nonlinear Polarization Rotation Phenomenon in Semiconductor Optical Amplifiers. (7th December 2011) - Said, Youssef; Rezig, Houria
Abstract : The focus of this paper is to analyze in detail the nonlinear polarization rotation phenomenon in the Semiconductor Optical Amplifier (SOA) according to the injection conditions. To this end, we have developed a numerical model based on the coupled mode theory and the formalism of Stokes. The obtained results are in agreement with the experimental measurements that have been carried out in free space, which allows optimum control and preservation of the polarization state of the injected and collected signals.